Fault Ride Through Strategy for Offshore Wind Farm Integration System via MMC-HVDC - Lijun Zhang; Yujun Zhong; Rui Chen; Yikai Sun; Jing Zhang; Ke Jia (MATEC Web of Conferences, 2018)
When offshore wind power is transmitted to ac grid through MMC-HVDC, the current and voltage will be quite different from those in traditional ac grid during grid side fault. This paper sets up an offshore wind farm integration system via MMC-HVDC and designs control strategies for each unit in the system. The fault ride through strategy of the system is proposed and its effectiveness has been verified. Thus, the AC bus voltage on wind farm side will stay stable during AC side fault. Once the chopper resistance is set properly, the output power and current of the wind farm can basically remain unchanged, which can successfully achieve fault isolation. The simulation results based on PSCAD have verified the theoretical analysis.